Cover Image, Volume 176A, Number 5, May 2018. Issue 5 (21st April 2018) - Kruszka, Paul; Porras, Antonio R.; de Souza, Deise Helena; Moresco, Angélica; Huckstadt, Victoria; Gill, Ashleigh D.; Boyle, Alec P.; Hu, Tommy; Addissie, Yonit A.; Mok, Gary T. K.; Tekendo‐Ngongang, Cedrik; Fieggen, Karen; et al.
Abstract : The cover image, by Paul Kruszka et al., is based on the Original Article Williams‐Beuren Syndrome in Diverse Populations, DOI: 10.1002/ajmg.a.38672